Three-dimensional Monte Carlo calculation of gas production in structural material of APEX reactor for some evaluated data files - Sarer, Basar; Hançerli̇oğullari, Aybaba; Gunay, Mehtap (Elsevier BV, 2013)
Abstract Proton and He-4 gas production rates in the structural material of a fusion-fission hybrid reactor were calculated with the three-dimensional Monte Carlo method by the MCNPX-2.5.0 code. We examined these reaction rates with five nuclear data libraries: ENDF/B-VII.0 T  = 300 K, JEFF-3.1 T  = 300 K, JENDL-4.0 T  = 300 K, ROSFOND T  = 300 K and CENDL-3.1 T  = 300 K. The production from each isotope of structural material made of ferritic steel was calculated. The neutron flux load is assumed to be 10 MW/m 2 .
Keywords: 7. Clean energy